Lumboperitoneal shunt and ventriculoperitoneal shunt for chronic hydrocephalus after aneurysmal subarachnoid hemorrhage: a comparison - Li, Xiaolei; Wang, Yuangang; Xia, Bin; Che, Hongmin; Yan, Zhongnan (Frontiers in Surgery, 2024)
Objective: Chronic hydrocephalus after aneurysmal subarachnoid hemorrhage (aSAH) results in poor neurological outcomes and cognitive deficits. Currently, the main treatments for chronic hydrocephalus include ventriculoperitoneal shunt (VPS) and lumboperitoneal shunt (LPS); however, the optimal treatment for chronic hydrocephalus after aSAH remains controversial.The records of 82 patients were retrospectively analyzed, and the patients were divided into VPS and LPS groups based on surgical methods. The efficacy, shunt successful rate and complications were compared. The assessments of treatment efficacy included the Evans index score (EIS), Keifer's hydrocephalus score (KHS), Mini-Mental State Examination (MMSE) score and functional independence measure (FIM). Patients were followed up for three months to observe the postoperative curative effects and complications.The rate of shunt obstruction was significantly higher in the LPS group than that in the VPS group (p < 0.05), and the shunt successful rate was significantly higher in the VPS group than that in the LPS group (p < 0.05). The total rate of complications was 24.4% for LPS and 39% for VPS. The improvements in EIS, KHS, MMSE, and FIM within each group after the shunt were significantly different compared to those before shunt (p < 0.05). Compared to those in the LPS group, the improvements in EIS, KHS, MMSE, and FIM were significantly different in the VPS group after shunt (p < 0.05).Compared with LPS, VPS in the treatment for chronic hydrocephalus after aSAH had greater therapeutic efficacy, as indicated by improved radiological outcomes, improved shunt successful rate, improved clinical outcomes, and improved quality of life. Therefore, we believe that VPS is the preferred treatment option for chronic hydrocephalus after aSAH, while LPS should only be used as an alternative to VPS.